Psychological Factors Influencing Entrepreneurship in Technology-Driven Contexts - joseph, Lily; S., Sharon (Journal of Advanced Research in Technological Entrepreneurship and Start-Up Incubation Ecosystems; Vol 1 No 1 (2025): Journal of Advanced Research in Technological Entrepreneurship and Start-Up Incubation Ecosystems, 2025)
Entrepreneurship in technology-driven sectors is marked by high levels of uncertainty, rapid technological advancements, and the constant need for innovation. Given the volatile and complex nature of these environments, understanding the psychological aspects of entrepreneurs becomes crucial for fostering long-term success in these ventures. This review delves into the psychological traits and mental processes that influence entrepreneurial behavior in the tech industry. It explores critical factors such as risk tolerance, resilience, self-efficacy, emotional intelligence, and decision-making under uncertainty. Additionally, the review investigates how cognitive biases—such as overconfidence and loss aversion—affect technology entrepreneurs’ decision-making and strategies. Emotions, stress management, and mental well-being are also highlighted as key psychological factors that influence entrepreneurial performance. Finally, the paper examines how support systems such as incubators, accelerators, and mentors can help entrepreneurs mitigate psychological challenges, build resilience, and cultivate a mindset conducive to innovation and venture growth. By identifying key psychological drivers and barriers in the entrepreneurial journey, this article provides practical insights for improving outcomes and sustainability for technology-driven startups.